One‐year cognitive follow‐up of COVID‐19 hospitalized patients. (29th March 2022) - Ferrucci, Roberta; Dini, Michelangelo; Rosci, Chiara; Capozza, Antonella; Groppo, Elisabetta; Reitano, Maria R.; Allocco, Elisa; Poletti, Barbara; Brugnera, Agostino; Bai, Francesca; Monti, Alessia; Ticozzi, Nicola; et al.
Abstract: Background and purpose: Cognitive dysfunction has been observed following recovery from COVID‐19. To the best of our knowledge, however, no study has assessed the progression of cognitive impairment after 1 year. The aim was to assess cognitive functioning at 1 year from hospital discharge, and eventual associations with specific clinical variables. Methods: Seventy‐six patients (aged 22–74 years) who had been hospitalized for COVID‐19 were recruited. Patients received neuropsychological assessments at 5 ( n  = 76) and 12 months ( n  = 53) from hospital discharge. Results: Over half (63.2%) of the patients had deficits in at least one test at 5 months. Compared to the assessment at 5 months, verbal memory, attention and processing speed improved significantly after 1 year (all p  < 0.05), whereas visuospatial memory did not (all p  > 0.500). The most affected domains after 1 year were processing speed (28.3%) and long‐term visuospatial (18.1%) and verbal (15.1%) memory. Lower PaO2 /FiO2 ratios in the acute phase were associated with worse verbal long‐term memory ( p  = 0.029) and visuospatial learning ( p  = 0.041) at 5 months. Worse visuospatial long‐term memory at 5 months was associated with hyposmia ( p  = 0.020) and dysgeusia ( p  = 0.037). Conclusion: Our study expands the results from previous studies showing that cognitive impairment can still be observed after 1 year. Patients with severe COVID‐19 should receive periodic cognitive follow‐up evaluations, as cognitive deficits in recovered patients could have social and occupational implications. Abstract : Cognitive impairment can still be observed in almost 50% of formerly hospitalized patients with COVID‐19 at 1 year from respiratory clinical recovery. Clinicians should be aware that the ratio of arterial oxygen partial pressure to fractional inspired oxygen and hyposmia/dysgeusia might represent risk factors for the development of cognitive impairment in COVID‐19.